Pengendalian Serangan Ganoderma spp. (60-80%) pada Tanaman Sengon sebagai Pelindung Tanaman Kopi dan Kakao - Elis Nina Herliyana; Darmono Taniwiryono; Hayati Minarsih; Muhammad Alam Firmansyah; Benyamin Dendang (Institut Pertanian Bogor, 2011)
Information about genetic variation of Ganoderma spp. As a couse of rot disease on plantation crops is necessary for consideration in efforts to protect crops. Exploration of the use of biological agents, especially Trichoderma spp., for the control of Ganoderma on forestry crops is still limited to laboratory testing. Its effectiveness to control Trichoderma spp. To protect plants in the nursery sengon being carried out, as well as to deternime its role in improving plant growth.